Professional and qualification development of enterprise personnel in terms of human capital theory - Samborskyi , Oleksandr; Renkas, Jurij (SPC Journal of Education, 2023)
The subject of the consideration of this article is the theoretically based concept of determining fair remuneration for the personnel of an enterprise who decide to continue their education or upgrade their professional skills. The basic theory that is taken in the article as the basis for determining the level of remuneration is the theory of human capital developed by M. Dobija. The model uses the capitalization rate, which determines the measure of spontaneous natural attrition of human capital and is related to the size of the constant a = 0.08 [1/year].